STRATEGI PENGEMBANGAN POTENSI WISATA 5 PANTAI DI KECAMATAN SAPTOSARI KABUPATEN GUNUNG KIDUL - Imam Arifa’illah Syaiful Huda; Muhammad Farouq Ghazali Matondang (Department of Geography Education, Faculty of Social Sciences, Universitas Negeri Medan, 2020)
The tourism sector has a positive influence on the economic growth of surrounding communities because the tourism sector can drive other sectors, such as the economic, social, and cultural sectors. Saptoari Subdistrict Gunung Kidul Regency has a large beach tourism potential for further development. Some beach tourism found in Saptosari Subdistrict are Nguyahan Beach, Ngobaran, Ngrenehan, Ngedan, and Butuh. According to data from the Department of Tourism, the number of tourists visiting Saptosari District has increased significantly. However, the beach tourism still has some problems and potential that have not yet been developed so that it inhibits the growth of tourism in the Saptosari District. This study aims to identify the characteristics of beaches in Saptosari Subdistrict, analyze potential and problems and develop tourism development strategies. This research is in the form of descriptive analytic with survey method and literature study. Data collection techniques through interviews, observation and documentation. While the analysis technique in research uses SWOT analysis. The results showed that the priority strategies that need to be carried out on 5 beaches are 1) developing tourist vehicles of all ages, 2) Organizing interesting events routinely (a calendar of regional/ national/ international events) by establishing cooperation with tourism management groups, 3) building telecommunications network, 4) The opening pringjono tourism area to expand tourist destinations in Nguyahan, 5) increasing product diversification typical for tourist souvenirs, 6) forming cleaning staff to create clean beaches, 7) developing culinary tourism (sea fish) and developing products interesting fish preparations, 8) design Ngeden Beach as a mainstay tour for special interests such as camping and tracking, 9) provide camping rental equipment and form a solid tourism management group to develop tourism, 10) provide special vehicle parking lots to look neatKeywords: SWOT, Development, Beach TourismSektor pariwisata memiliki pengaruh yang positif terhadap pertumbuhan ekonomi masyarakat sekitar karena sektor pariwisata mampu menggerakkan sektor-sektor lainnya, seperti sektor ekonomi, sosial, dan budaya. Kecamatan Saptoari Kabupaten Gunung Kidul memiliki potensi wisata pantai yang besar untuk dikembangkan lebih lanjut. Beberapa wisata pantai yang terdapat di Kecamatan Saptosari yaitu Pantai Nguyahan, Ngobaran, Ngrenehan, Ngedan, dan Butuh. Menurut data Dinas Pariwisata jumlah wisatawan yang datang ke Kecamatan Saptosari mengalami peningkatan secara signifikan. Namun, wisata pantai tersebut masih memiliki beberapa masalah dan potensi yang belum dikembangkan sehingga menghambat pertumbuhan pariwisata di Kecamatan Saptosari. Penelitian ini bertujuan untuk mengidentifikasi karakteristik pantai di Kecamatan Saptosari, menganalisis potensi dan masalah serta menyusun strategi pengembangan pariwisata. Penelitian ini berupa deskriptif analitik dengan metode survei dan studi literatur. Teknik pengumpulan data melalui wawancara, observasi dan dokumentasi. Sedangkan teknik analisis dalam penelitian menggunakan analisis SWOT. Hasil penelitian menunjukan bahwa strategi prioritas yang perlu dilakukan pada 5 pantai yaitu 1) mengembangkan wahana wisata dari segala umur, 2) Mengadakan event yang menarik secara rutin (kalender event regional/nasional/international) dengan menjalin kerjasama dengan kelompok pengelola pariwisata, 3) membangun jaringan telekomunikasi, 4) membuka kawasan wisata pringjono untuk memperluas destinasi wisata di Nguyahan, 5) meningkatkan diversifikasi produk yang khas untuk cinderamata wisatawan, 6) membentuk petugas kebersihan agar tercipata pantai yang bersih, 7) mengembangan wisata kuliner (Ikan laut) dan mengembangkan produk olahan ikan yang menarik, 8) mendesain Pantai Ngeden sebagai wisata andalan untuk minat khusus seperti camping dan tracking, 9) Menyediakan alat penyewaan camping dan membentuk kelompok pengelola pariwisata yang solid untuk mengembangkan pariwisata, 10) menyediakan lahan parkir kendaraan khusus agar terlihat rapiKata Kunci: SWOT, Pengembangan, Wisata Pantai